Pengaruh Keunikan Signature Look Riasan Di Instagram Terhadap Self Confidence Pada Makeup Artist Di Kediri - Nadia Fajrina Nurma Agustin; Dindy Sinta Megasari; Mutimmatul Faidah; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2026)
This study was motivated by the growing use of Instagram as a personal branding medium for Make Up Artists (MUAs), where the uniqueness of makeup signature looks is assumed to influence MUAs’ self-confidence in showcasing their work and promoting their services. This study aimed to determine the description of makeup signature look uniqueness on Instagram, the description of self-confidence, and the influence of makeup signature look uniqueness on Instagram toward self-confidence among Make Up Artists in Kediri. This study used a quantitative approach with a descriptive correlational research design. The research was conducted in Kediri involving 50 active Instagram-user Make Up Artists as research subjects. Data collection techniques included questionnaires using a 1–4 Likert scale and direct observation of MUA Instagram accounts. The research instruments consisted of questionnaires regarding makeup signature look and self-confidence based on research indicators. Data analysis techniques used descriptive percentage analysis and simple linear regression with the assistance of SPSS. The results showed that the uniqueness of makeup signature look was categorized as very high with a percentage of 79.67%, while self-confidence was also categorized as very high with a percentage of 83.25%. Regression test results indicated that the uniqueness of makeup signature look on Instagram had a positive and significant effect on self-confidence among Make Up Artists in Kediri with a significance value of 0.000 < 0.05 and an effect contribution of 48.8%. The conclusion of this study is that the higher the uniqueness of the makeup signature look owned by MUAs, the higher their self-confidence. It is suggested that MUAs continue developing their distinctive makeup styles to strengthen personal branding and increase self-confidence. Keywords: signature look, Instagram, self-confidence, make up artist, personal branding